Penguatan Branding Berbasis Nilai Syariah bagi UMKM melalui Pendekatan Participatory Action Research - Arfik, Umi Alfiatul; Nabila, Aisya; Nuraini, Khusnia; Mutamainnah, Fatiya Auliyana; Ayatulloh, Mohammad Iqbal; Anhar, Mohammad Agus Zam-Zam Tajuddin; Arianto, Achmad Rafi; Subagyo, Ahmad Aditya Wahyu (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth, including in the traditional culinary sector. Gudeg Bu Anjar in Kediri is a culinary specialty from Yogyakarta that is popular with people outside its region of origin. Although it has partnered with online delivery services and is active on social media, its promotional reach is still not optimal. In addition, business owners demonstrate a commitment to the principle of prudence in transactions and hold halal certificates that strengthen consumer confidence. This dedication aims to strengthen sharia-based branding strategies through the optimization of digital and offline promotion. The methods used are Participatory Action Research (PAR) through the production of creative content on Instagram and TikTok, brochure distribution, and sharia-based branding education. The results of the assistance show that digital engagement and promotional reach have increased, the halal identity of businesses has become more prominent, and the application of sharia business ethics has been integrated into marketing strategies.